(E)-1-(4-Chlorophenyl)ethanone semicarbazone - Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title compound, C(9)H(10)ClN(3)O, the semicarbazone group is approximately planar, with an r.m.s. deviation from the mean plane of 0.054 (1) Å. The dihedral angle between the least-squares planes through the semicarbazone group and the benzene ring is 30.46 (5)°. In the solid state, molecules are linked via intermolecular N—H⋯O and N—H⋯N hydrogen bonds, generating R (2) (2)(9) ring motifs which, together with R (2) (2)(8) ring motifs formed by pairs of intermolecular N—H⋯O hydrogen bonds, lead to the formation of a seldom-observed molecular trimer. Furthermore, N—H⋯O hydrogen bonds form R (2) (1)(7) ring motifs with C—H⋯O hydrogen bonds, further consolidating the crystal structure. Molecules are linked by these intermolecular interactions, forming two-dimensional networks parallel to (100).